Total Synthesis of Ophiorrhine A, G and Ophiorrhiside E Featuring a Bioinspired Intramolecular Diels–Alder Cycloaddition. (10th August 2022) - Cao, Wei; Dou, Yingchao; Kouklovsky, Cyrille; Vincent, Guillaume
Abstract: We report the first total synthesis of the monoterpene indole alkaloids ophiorrhine A via a late stage bioinspired intramolecular Diels–Alder cycloaddition to form the intricate bridged and spirannic polycyclic system. Several strategies were investigated to construct the indolopyridone moiety of ophiorrhiside E, the postulated biosynthetic precursor of ophiorrhine A. Eventually, the Friedel–Crafts‐type coupling of N‐methyl indolyl‐acetamide with a secologanin‐derived acid chloride delivered ophiorrhine G. Cyclodehydration of a protected form of the latter was followed by the desired spontaneous intramolecular Diels–Alder cycloaddition of protected ophiorrhiside E leading to ophiorrhine A. Abstract : A late stage bioinspired intramolecular Diels–Alder cycloaddition of the indolopyridone of ophiorrhiside E was deployed to access the spirocyclic azabicyclic[2.2.2]octanone ring system of ophiorrhiside A and achieve its total synthesis. The indolopyridone of ophiorrhiside E was synthesized by the cyclodehydration of ophiorrhine G which was formed by the acylation of N‐methyl indolylacetamide by a secologanin derivative.